Swarming Magnetic Photoactive Microrobots for Dental Implant Biofilm Eradication - Mayorga-Martinez, Carmen C; Zelenka, Jaroslav; Klima, Karel; Mayorga-Burrezo, Paula; Hoang, Lan; Ruml, Tomas; Pumera, Martin (ACS nano, 2022)
Titanium dental implants are a multibillion dollar market in the United States alone. The growth of a bacterial biofilm on a dental implant can cause gingivitis, implant loss, and expensive subsequent care. Herein, we demonstrate the efficient eradication of dental biofilm on titanium dental implants via swarming magnetic microrobots based on ferromagnetic (Fe3O4) and photoactive (BiVO4) materials through polyethylenimine micelles. The ferromagnetic component serves as a propulsion force using a transversal rotating magnetic field while BiVO4 is the photoactive generator of reactive oxygen species to eradicate the biofilm colonies. Such photoactive magnetically powered, precisely navigated microrobots are able to destroy biofilm colonies on titanium implants, demonstrating their use in precision medicine.
Keywords: micromotors; Biofilms; bacterial biofilm; polymer micelles; ferromagnetic material; Magnetic Phenomena; povrchové vlastnosti; Titanium; Dental Implants; magnetické jevy; biofilmy; zubní implantáty; titan; photoactive material; Surface Properties